(3jfHhY GdMjGI hgh JaSjQ ddbQBfs - (3MLI GdOjf CHh YHO Gddg eMeO Hf YHO Gddg Hf XaQ GdUbdj Gdecj, GHf XaQ,J (B565 (3g` s
(3ChdgG (B:s
(3JaSjQ GdBjI GdChdi ef ShQI GdeGFOI s
(3BNQgG (B:s
(3JaSjQ GdBjI GdCNjQI ef ShQI ghO s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B230s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B51 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B2052s
Keywords: (3GdJaSjQ hYdhe GdbQBfs